The validity and accuracy of 3D-printed patient-specific instruments for high tibial osteotomy: a cadaveric study - Zhuang Miao; Songlin Li; Desu Luo; Qunshan Lu; Peilai Liu (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Objective High tibial osteotomy (HTO) has been used for the treatment of patients with knee osteoarthritis. However, the successful implementation of HTO requires precise intraoperative positioning, which places greater requirements on the surgeon. In this study, we aimed to design a new kind of 3D-printed patient-specific instrument (PSI) for HTO, including a positioning device and an angle bracing spacer, and verify its effectiveness using cadaveric specimens. Methods This study included ten fresh human lower-limb cadaveric specimens. Computed tomography (CT) and X-ray examinations were performed to make preoperative plans. PSI was designed and 3D-printed according to the preoperative plan. Then, the PSI was used to guide HTO. Finally, we performed X-ray and CT after the operation to verify its validity and accuracy. Results The PSI using process was adjusted according to the pre-experimental procedure in 1 case. Hinge fracture occurred in 1 case. According to X-rays of the remaining eight cadaveric specimens, no statistically significant difference was noted between the preoperative planning medial proximal tibial angle (MPTA) and postoperative MPTA (P > 0.05) or the preoperative and postoperative posterior slope angle (PSA) (P > 0.05). According to the CT of 10 cadaveric specimens, no statistically significant difference was noted between the design angle and actual angle, which was measured according to the angle between the osteotomized line and the cross section (P > 0.05). The gap between the designed osteotomy line and the actual osteotomy line was 2.09 (0.8 ~ 3.44) mm in the coronal plane and 1.58 (0.7 ~ 2.85) mm in the sagittal plane. Conclusion This 3D-printed PSI of HTO accurately achieves the angle and position of the preoperative plan without increasing the stripping area. However, its use still requires a certain degree of proficiency to avoid complications, such as hinge fracture.